Exploring the experiences of stalking within one Scottish health board: a survey of mental health professionals - Bolton, Judi (The journal of forensic psychiatry & psychology, 2022)
In recent years, the prevalence of stalking within the mental health profession has received considerable attention. Despite this focus, much less is known about the experience of stalking both in and out of the workplace and actions taken in response to stalking. This study aimed to examine the extent, characteristics and impact of stalking behaviours on mental health staff employed in one NHS Health Board in Scotland. A questionnaire was distributed to all mental health staff. Of the 353 responses, 31% (n = 108) had experienced stalking according to the legal definition. Of those who had experienced stalking at work 54% (n = 37) were stalked by a patient, 30% (n = 21) by a colleague, 6% (n = 4) by a patient’s relative or carer and 10% (n = 7) were stalked by someone else at work. Over half of the respondents who had experienced stalking believed their stalker had a psychiatric disorder. The most common ‘type’ of stalker identified was ‘incompetent suitor. Stalking had a negative impact on the wellbeing of staff. These findings have important implications for healthcare services in both the clinical care of patients and healthcare policy to address staff experiences of stalking.